A Laboratory Market Investigation of Low Balling in Audit Pricing. - Schatzberg, Jeffrey W. (The Accounting Review, 1990)
Examines the economic rationale of the low-balling practice in audit pricing. Analysis of the practice using experimental economic methodology; Testing of low-balling under different conditions of transaction costs.